SCHOOL PRINCIPLE MANAGEMENT IN IMPROVING TEACHER COMPETENCE TOWARD STUDENTS' MORAL DEVELOPMENT AT SDIT AL-FADIYAH IN GOWA DISTRICT - Soegono, Soegono; Malli, Rusli; Ali Bakri, Muhammad; Dewanti Palangkey, Rahmi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
This research is about the principal’s management in improving teacher competence regarding student moral development at SDIT Al-Fadiyah. This study aims to: 1) Develop managerial abilities of school principals in increasing teacher competence at SDIT Al-Fadiyah, 2) Developing forms of moral development at SDIT Al-Fadiyah in Gowa, 3) Understanding the principal's strategy for increasing teacher competence in developing participant morals studied at SDIT Al-Fadiyah. This study uses a qualitative research approach, researchers use data collection analysis by observation, interviews, and documentation. The data sources for this study were school principals, deputy principals, teachers, student representatives and other information deemed necessary in this study. The data were analyzed by qualitative descriptive analysis relating to the Management of Principals in Improving Teacher Competence Against the Moral Development of Students at SDIT Al Fadiyah Gowa. The results of the study are as follows: First: the managerial ability of the principal in improving teacher competence includes: planning, organizing, implementing, supervising. Second: The form of moral development of students at SDIT Al-Fadiyah Gowa has been going well starting with the formulation of moral development goals, compiling moral development programs, using lecture methods, direct practice, discussions, exemplary and giving awards. Third: The principal's strategy in improving teacher competency in moral development includes: carrying out functional education and training, empowering KKG and carrying out teacher supervision.